Iron-based soft magnetic powder for pressed powder magnetic core, pressed powder magnetic core and method for manufacturing the same
By forming a continuous film of condensed aluminum phosphate and silicone resin layer on the iron-based soft magnetic powder, the problems of high iron loss and low magnetic flux density of the powdered magnetic core are solved, and the effects of high density and low iron loss are achieved , and avoid problems of oxidation and high cost.
Patent Information
- Application Number
- CN202080099230.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-04-02
- Filing Date
- 2020-12-18
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2040-12-18
AI Technical Summary
The iron loss of the existing powdered magnetic core is high and the magnetic flux density is low, making it difficult to achieve the effects of high density and low iron loss, especially in the medium and high frequency range, and the phosphoric acid-based film used in the prior art can easily lead to iron. Powder oxidation, high cost and safety problems exist.
A condensed aluminum phosphate layer is formed on the particle surface of the iron-based soft magnetic powder, and a silicone resin layer is attached to the layer. Combined with the characteristics of the condensed aluminum phosphate and silicone resin, a continuous film is formed to achieve high density and low iron loss. The dry method is used to avoid oxidation and high-temperature annealing to maintain insulation.
The high density and low iron loss of the powdered magnetic core are achieved, the hysteresis loss is reduced, the flux density is improved, the insulation is enhanced, the oxidation problem is avoided and the manufacturing cost is reduced.
Smart Images

Figure BDA0003868920650000111 
Figure BDA0003868920650000131 
Figure BDA0003868920650000141
Abstract
Description
Technical Field
[0001] The invention relates to iron-based soft magnetic powder for pressed powder magnetic core, pressed powder magnetic core and a method for manufacturing the same. Background Art
[0002] Magnetic cores used in motors, transformers, etc. require high magnetic flux density and low iron loss. Conventionally, cores made of laminated electromagnetic steel sheets have been used for motor magnetic cores, but in recent years, powder magnetic cores have attracted much attention.
[0003] The biggest feature of the powder core is that it can form a three-dimensional magnetic circuit. When electromagnetic steel sheets are used as materials, the core is formed by stacking, so the degree of freedom of shape is limited. On the other hand, the powder core is obtained by pressing soft magnetic particles with an insulating film, and the shape can be changed by changing the mold, which can obtain a degree of freedom in shape that exceeds that of electromagnetic steel sheets.
[0004] In addition, compared with the process of laminating electromagnetic steel sheets, the process steps required for press molding are short and inexpensive, and the powder used as the base is also inexpensive, so the powder core has excellent cost performance.
[0005] In addition, when electromagnetic steel sheets are used as materials, the steel sheets with insulated surfaces are stacked, so the magnetic characteristics are different in the surface direction of the steel sheets and in the direction perpendicular to the surface, and the magnetic characteristics in the direction perpendicular to the surface are poor, which has the disadvantage that. On the other hand, the particles of the powder core are independently covered with an insulating film, so the magnetic characteristics are uniform in all directions, which is advantageous for the formation of a three-dimensional magnetic circuit.
[0006] In this way, the powder core can not only realize the design of three-dimensional magnetic circuit, but also has excellent cost performance. Considering these aspects, in order to achieve the miniaturization, rare earth-free, and low-cost requirements of motors in recent years, the research and development of motors with three-dimensional magnetic circuits using powder cores has increased.
[0007] Here, as the motor is miniaturized, the importance of reducing the iron loss at medium and high frequencies (800Hz to 3kHz) becomes particularly important due to the high-speed rotation that accompanies the miniaturization. However, compared with electromagnetic steel sheets, the iron loss of the powder core is large and the magnetic flux density is low, so there are currently few examples of practical implementation.
[0008] For the practical application of powder cores, it is important to ensure the insulation between particles not only at the stage of the molded body, but also when the molded body is subjected to stress relief annealing at high temperature (for example, 600°C) to reduce the iron loss of the powder core at medium and high frequencies. In addition, it is also important to increase the magnetic flux density, so it is necessary to increase the density of the powder core.
[0009] As for the soft magnetic powder for the powder magnetic core, for example, Patent Documents 1 to 3 propose an iron-based soft magnetic powder for the powder magnetic core having a silicone resin on a phosphate-based coating.
[0010] In addition, Patent Document 4 proposes a soft magnetic powder in which a specified amount of condensed phosphate metal salt is mixed into the soft magnetic powder to form a coating of the condensed phosphate metal salt around the soft magnetic powder, and Patent Document 5 proposes a soft magnetic powder in which a specified amount of condensed phosphate metal compound is mixed and further mixed with insulating fine powder to form a coating layer containing the condensed phosphate metal compound around the soft magnetic powder.
[0011] Furthermore, Patent Document 6 proposes a soft magnetic material having Fe—Si alloy powder and an insulating film covering the surfaces of particles in the Fe—Si alloy powder, wherein the insulating film has a silicone oligomer layer and a silicone resin layer.
[0012] Prior art literature
[0013] Patent Literature
[0014] Patent Document 1: Japanese Patent Application Publication No. 2012-84803
[0015] Patent Document 2: Patent No. 4044591
[0016] Patent Document 3: International Publication No. 2012 / 124032
[0017] Patent Document 4: Japanese Patent Application Publication No. 2014-236118
[0018] Patent Document 5: Japanese Patent Application Publication No. 2015-230930
[0019] Patent Document 6: Japanese Patent Application Publication No. 2019-151909 Summary of the invention
[0020] However, in Patent Documents 1 to 3, a diluted aqueous solution of orthophosphoric acid is used when forming a phosphoric acid-based coating on the iron powder. Compared with bulk materials, iron powder has a larger specific surface area and is easily oxidized when exposed to moisture such as an aqueous solution. The oxidation of iron powder will lead to an increase in hysteresis loss when the powdered magnetic core is made, and there is a problem that the iron loss cannot be fully reduced. In addition, Patent Document 4 points out that when a diluted aqueous solution of orthophosphoric acid is used, the iron-based soft magnetic powder for the powdered magnetic core may become hygroscopic due to free orthophosphoric acid. The problem of free orthophosphoric acid cannot be avoided even when a solution of orthophosphoric acid in an organic solvent is used. In addition, the use of organic solvents has problems such as high cost and ignition, so safety measures are required, and dedicated manufacturing equipment is required, which is a heavy burden.
[0021] In order to ensure the moldability of the compressed powder core in Patent Documents 4 and 5, a large amount of binding resin needs to be further added to the mixture of soft magnetic powder and powder of condensed phosphate metal salt or condensed phosphate compound, i.e., the soft magnetic powder. The amount of binding resin exceeds 2.0 mass % in the embodiments of these documents. Therefore, it is difficult to achieve high density of the compressed powder core.
[0022] Patent Document 6 is specifically designed to meet the extremely limited demand for lowering the magnetic permeability of powder magnetic cores. Therefore, it is necessary to cover a large amount of Fe-Si alloy powder with a specific insulating coating layer, and thus it is still difficult to achieve high density of powder magnetic cores using this powder.
[0023] The present invention has been developed in view of the above-mentioned actual situation, and an object of the present invention is to provide an iron-based soft magnetic powder for a dust core that can achieve high density and low iron loss of the dust core.
[0024] The inventors of the present invention have conducted repeated studies and found that by making condensed aluminum phosphate, which has good adhesion to iron-based soft magnetic powder, adhere to the surface of particles in the iron-based soft magnetic powder as a continuous film, and then interposing a silicone resin with good heat resistance in between the continuous film, the properties of the condensed aluminum phosphate layer and the silicone resin layer can be combined, and good insulation can be exerted even in a small amount, thereby achieving high density and low iron loss in the powder core, thereby completing the present invention.
[0025] The gist of the present invention is as follows.
[0026] [1] An iron-based soft magnetic powder for a powder magnetic core, wherein the particles in the iron-based soft magnetic powder have a condensed aluminum phosphate layer on their surfaces, and a silicone resin layer on the surface of the condensed aluminum phosphate layer,
[0027] The condensed aluminum phosphate layer is a continuous film.
[0028] The total mass of the condensed aluminum phosphate layer and the silicone resin layer is 0.60 mass % or less in 100 mass % of the total mass of the iron-based soft magnetic powder, the condensed aluminum phosphate layer and the silicone resin layer.
[0029] [2] The iron-based soft magnetic powder for a powder magnetic core according to [1], wherein the total mass of the condensed aluminum phosphate layer and the silicone resin layer is 0.10% to 0.60% by mass in the total mass of the iron-based soft magnetic powder, the condensed aluminum phosphate layer and the silicone resin layer (100% by mass).
[0030] [3] The iron-based soft magnetic powder for a dust core according to [1] or [2], wherein the mass ratio of the condensed aluminum phosphate layer to the total mass of the condensed aluminum phosphate layer and the silicone resin layer is 0.2 to 0.9.
[0031] [4] A powder magnetic core obtained by pressing and molding the powder magnetic core of any one of [1] to [3] using iron-based soft magnetic powder and subjecting the pressed powder magnetic core to heat treatment.
[0032] [5] A method for producing an iron-based soft magnetic powder for a powder magnetic core, the method comprising: providing a condensed aluminum phosphate layer on the surface of particles in the iron-based soft magnetic powder, and providing a silicone resin layer on the surface of the condensed aluminum phosphate layer;
[0033] The method comprises the following steps: heating and mixing an iron-based soft magnetic powder and a condensed aluminum phosphate powder to obtain an iron-based soft magnetic powder having a condensed aluminum phosphate layer on the surface, and then attaching an organic silicone resin to the surface of the condensed aluminum phosphate layer to form an organic silicone resin layer.
[0034] The total mass of the condensed aluminum phosphate powder and the silicone resin is 0.60 mass % or less in 100 mass % of the total mass of the iron-based soft magnetic powder, the condensed aluminum phosphate powder and the silicone resin.
[0035] [6] The method for producing an iron-based soft magnetic powder for a powder magnetic core according to [5], wherein the maximum temperature reached during the heating and mixing is 100°C to 200°C.
[0036] [7] A method for producing an iron-based soft magnetic powder for a powdered magnetic core according to [5] or [6], wherein the silicone resin is attached to the surface of the condensed aluminum phosphate layer by kneading a solution in which a silicone resin is dissolved in an organic solvent and an iron-based soft magnetic powder having a condensed aluminum phosphate layer, followed by drying.
[0037] [8] The method for producing an iron-based soft magnetic powder for a powder magnetic core according to [5] or [6], wherein a solid silicone resin and the iron-based soft magnetic powder having a condensed aluminum phosphate layer are mixed to allow the silicone resin to adhere to the surface of the condensed aluminum phosphate layer.
[0038] [9] A method for producing an iron-based soft magnetic powder for a powdered magnetic core according to any one of [5] to [8], wherein the total mass of the condensed aluminum phosphate powder and the silicone resin is 0.10% to 0.60% by mass in the total mass of the iron-based soft magnetic powder, the condensed aluminum phosphate powder and the silicone resin being 100% by mass.
[0039]
[10] The method for producing an iron-based soft magnetic powder for a powder magnetic core according to any one of [5] to [9], wherein the mass ratio of the condensed aluminum phosphate powder to the total mass of the condensed aluminum phosphate powder and the silicone resin is 0.2 to 0.9.
[0040]
[11] A method for manufacturing a powdered magnetic core, comprising the following steps: filling a mold with the iron-based soft magnetic powder for a powdered magnetic core of any one of [1] to [3] or the iron-based soft magnetic powder for a powdered magnetic core obtained by the method for manufacturing an iron-based soft magnetic powder for a powdered magnetic core of any one of [5] to
[10] , pressing and molding, and then subjecting the mold to heat treatment at a temperature of not less than 500°C and not more than 900°C.
[0041] According to the present invention, there are provided an iron-based soft magnetic powder for a dust core capable of achieving high density and low iron loss in a dust core, and a method for producing the same.
[0042] Furthermore, according to the present invention, a high-density, low-iron-loss powder magnetic core and a method for manufacturing the same are provided. DETAILED DESCRIPTION
[0043] The present invention is described in detail below. The iron-based soft magnetic powder for pressed powder magnetic cores of the present invention has a condensed aluminum phosphate layer on the surface of the particles in the iron-based soft magnetic powder, and has a silicone resin layer on the surface of the condensed aluminum phosphate layer. That is, the iron-based soft magnetic powder for pressed powder magnetic cores of the present invention is composed of an iron-based soft magnetic powder, a condensed aluminum phosphate layer and a silicone resin layer, which have these in order from the inside. The condensed aluminum phosphate layer and the silicone resin layer act as insulating layers in the iron-based soft magnetic powder for pressed powder magnetic cores of the present invention.
[0044] <Iron-based soft magnetic powder>
[0045] The iron-based soft magnetic powder is not particularly limited, and examples thereof include pure iron powder, iron-based alloy powder (e.g., powders of Fe-Al alloy, Fe-Si alloy, sendust, permalloy, etc.), iron-based amorphous powder, etc. Pure iron powder is preferred in terms of good compressibility and ease of high density, and water-atomized pure iron powder is preferred in terms of being relatively inexpensive to obtain.
[0046] Iron-based soft magnetic powder can use an apparent density of 2.8Mg / m 3 The above powder has an average particle size of 10 μm to 200 μm.
[0047] If the apparent density is within the above range, the obtained iron-based soft magnetic powder for powder magnetic core can be easily used to produce a high-density powder magnetic core. The upper limit of the apparent density is not particularly limited, but can generally be 5.0 Mg / m 3 the following.
[0048] If the average particle size is within the above range, the fluidity of the iron-based soft magnetic powder for the powder core is sufficient and can be easily filled into the mold during the manufacture of the powder core. In order to fully suppress the eddy current loss of the powder core, it is preferred to adjust the average particle size according to the intended use. For example, the average particle size can be 60 μm to 200 μm, which is preferred when considering the manufacture of a motor core, for example.
[0049] Here, the average particle size of the iron-based soft magnetic powder is the median diameter D50 based on weight, that is, the particle size at which the larger particle size and the smaller particle size become equal in weight when the powder is divided into two particles at a certain particle size.
[0050] <Condensed aluminum phosphate layer>
[0051] By heating and mixing the iron-based soft magnetic powder and the condensed aluminum phosphate powder, a condensed aluminum phosphate layer can be formed on the surface of the particles in the iron-based soft magnetic powder. Such a condensed aluminum phosphate layer can be formed by a dry method without using a solvent such as water, so the problem of oxidation of the iron-based soft magnetic powder can be avoided. In addition, since a step of dissolving in a solvent is not required, it is also advantageous in terms of equipment and workability.
[0052] The condensed aluminum phosphate layer formed by heating and mixing forms a continuous film. Here, the continuous film can be a complete coating or a partial coating, and the powders are fused to each other and the coated part is continuous, which is different from the state where the powders are directly scattered and attached. It is preferred that the continuous film covers most of the surface of the particles in the iron-based soft magnetic powder, and more preferably substantially covers the entire surface. It is speculated that the excellent adhesion of the iron-based soft magnetic powder to the surface of the condensed aluminum phosphate layer is due to the reaction at the interface between the continuous film of the condensed aluminum phosphate and the iron-based soft magnetic powder.
[0053] Examples of condensed aluminum phosphate include aluminum tripolyphosphate, aluminum metaphosphate, and mixtures thereof, which are obtained by heating and reacting first aluminum phosphate. Among them, aluminum dihydrogen tripolyphosphate is preferred.
[0054] The average particle size of the condensed aluminum phosphate powder can be 1 μm to 10 μm. If it is within the above range, the fluidity is sufficient, good workability is obtained, and a uniform continuous film can be easily formed. The average particle size is preferably 1.5 μm or more, and preferably 7.5 μm or less.
[0055] Here, the average particle size of the condensed aluminum phosphate powder is a volume-based median diameter D50 measured by a laser diffraction method.
[0056] The iron-based soft magnetic powder and the condensed aluminum phosphate powder can be heated and mixed using a rotary blade mixer, for example, the FM series of Coke Co., Ltd. and the high-speed mixer series of EarthTechnica Co., Ltd.
[0057] The rotating speed of the mixer is not particularly limited and may be 100 rpm to 1000 rpm. If it is within the above range, a continuous film can be effectively formed, and excessive high-speed stirring can be avoided to cause plastic deformation of the soft magnetic powder, resulting in reduced compressibility and increased hysteresis loss. The rotating speed is preferably 200 rpm or more, and preferably 800 rpm or less.
[0058] The heated mixing can be heated in such a manner that the highest temperature reached during mixing is 100°C to 200°C. If it is within the above range, a continuous film of condensed aluminum phosphate can be easily formed on the surface of the particles in the iron-based soft magnetic powder, and the condensed aluminum phosphate can be easily prevented from being deteriorated due to high temperature. The highest temperature reached during mixing is preferably 130°C or more, more preferably 150°C or more. It should be noted that the temperature referred to here refers to the temperature of the powder during mixing, and when a rotary blade mixer is used, the temperature indicated by a thermocouple protruding from the tank wall of the stirring tank to a degree that does not contact the rotary blade.
[0059] The maximum temperature reached during mixing refers to the highest temperature of the powder during mixing, and may be the highest temperature of the powder containing the iron-based soft magnetic powder and the condensed aluminum phosphate powder measured by the thermocouple.
[0060] From the viewpoint of suppressing oxidation of the iron-based soft magnetic powder, the heating and mixing is preferably performed in an inert gas atmosphere, for example, a nitrogen atmosphere.
[0061] From the perspective of suppressing oxidation, after heating and mixing, the iron-based soft magnetic powder having a condensed aluminum phosphate layer is preferably discharged from the mixer after the powder temperature reaches 80° C. or less, and more preferably after the powder temperature reaches 60° C. or less. The lower limit of the temperature of the powder during discharge is not particularly limited, and may be, for example, room temperature (0 to 30° C.) or above.
[0062] During heating and mixing, insulating fine powder (Al2O3, SiO2, MgO, etc.), alkaline substances (Al2O3, SiO2, MgO, Mg(OH)2, CaO, asbestos, talc, fly ash, etc.), etc. may be further added to the iron-based soft magnetic powder and condensed aluminum phosphate powder, but from the perspective of forming a continuous film, it is preferably not added.
[0063] <Silicone resin>
[0064] Since silicone resin forms Si—O bonds with excellent heat resistance by heat treatment, it is possible to maintain excellent insulation even when stress relief annealing is performed on the molded body at a high temperature (eg, 600° C.) during the production of the powder magnetic core.
[0065] As the silicone resin, a resin-based silicone resin can be cited, for example, a silicone resin having a trifunctional T unit of 60 mol% or more. Among them, a silicone resin having methyl groups of 50 mol% or more of the functional groups on Si is preferred, for example, a methylphenyl silicone resin (KR255, KR311, KR300, etc. manufactured by Shin-Etsu Chemical Co., Ltd.), a methyl silicone resin (KR251, KR400, KR220L, KR242A, KR240, KR500, KC89, etc. manufactured by Shin-Etsu Chemical Co., Ltd.) can be cited. SR2400 and TREFIL R910 manufactured by Toray Dow Corning can also be used.
[0066] The silicone resin can be attached to the surface of the condensed aluminum phosphate layer by a wet method using an organic solvent or a dry method without using a solvent. The dry method is preferred because it does not require safety measures associated with the use of an organic solvent and is advantageous in terms of cost, equipment, and workability.
[0067] In the case of the wet method, the silicone resin can be attached by kneading a solution in which the silicone resin is dissolved in an organic solvent and the iron-based soft magnetic powder having a condensed aluminum phosphate layer and drying the mixture.
[0068] Examples of the organic solvent include petroleum-based organic solvents such as alcohols, xylene, and toluene. The solid content concentration of the silicone resin in the solution may be 1 to 10% by mass. Drying may be performed in the air. The drying temperature may be a temperature at which the organic solvent used volatilizes and is lower than the curing temperature of the silicone resin.
[0069] In the case of the wet method, as the silicone resin, SR2400 manufactured by Dow Corning Toray Co., Ltd., KR-311, LR-220L manufactured by Shin-Etsu Chemical Co., Ltd., or the like is preferably used.
[0070] In the case of the dry method, the silicone resin can be attached by mixing a solid silicone resin and the iron-based soft magnetic powder having a condensed aluminum phosphate layer.
[0071] A rotary blade type mixer can be used for mixing, and examples thereof include the mixers exemplified in the formation of the condensed aluminum phosphate layer.
[0072] The rotation speed of the mixer may be 100 rpm to 2000 rpm. Within the above range, the silicone resin can be effectively attached and excessive high-speed stirring can be avoided. The rotation speed is preferably 200 rpm or more and preferably 1500 rpm or less.
[0073] The mixing may be performed by starting mixing at room temperature and discharging the powder outside the mixer when the powder temperature reaches 40°C to 70°C.
[0074] The solid silicone resin is not particularly limited, and a powdery, sheet-like silicone resin, etc. can be used. Among them, any shape is preferably used as long as it softens by heat.
[0075] As the silicone resin, TREFIL R-910 manufactured by Dow Corning Toray Co., Ltd. or KR-220LP manufactured by Shin-Etsu Chemical Co., Ltd. is preferably used.
[0076] When the silicone resin is attached, a lubricant (for example, metal soaps such as lithium stearate, zinc stearate, and calcium stearate, and waxes such as fatty acid amide) may be added together with the silicone resin.
[0077] After the silicone resin is attached by a wet method or a dry method, a heat treatment is performed to increase the hardness of the attached silicone resin. The temperature of the heat treatment may be 150° C. to 250° C. The heat treatment may be performed in the air or in an inert gas atmosphere (eg, a nitrogen atmosphere).
[0078] <Condensed aluminum phosphate layer and silicone resin layer>
[0079] In the iron-based soft magnetic powder for the pressed powder core of the present invention, the characteristics of the condensed aluminum phosphate layer and the silicone resin layer are combined to exert good insulation properties. Therefore, from the perspective of high density of the pressed powder core, sufficient insulation properties can be obtained even if the total mass of the condensed aluminum phosphate layer and the silicone resin layer is less than 0.60 mass% relative to the total mass of 100 mass% of the iron-based soft magnetic powder, the condensed aluminum phosphate layer and the silicone resin.
[0080] From the perspective of insulation, the total mass of the condensed aluminum phosphate layer and the silicone resin layer is preferably 0.10 mass % or more, more preferably 0.30 mass % or more, and from the perspective of high density, the total mass of the condensed aluminum phosphate layer and the silicone resin layer is preferably 0.50 mass % or less.
[0081] From the perspective of ensuring the adhesion between the condensed aluminum phosphate layer and the iron-based soft magnetic layer and improving the heat resistance of the silicone resin, when the total mass of the condensed aluminum phosphate layer and the silicone resin layer is set to 1, the mass ratio of the condensed aluminum phosphate layer is preferably 0.2 to 0.9, and more preferably 0.3 to 0.8.
[0082] The ratio of the combined mass of the condensed aluminum phosphate layer and the silicone resin layer to 100% by mass of the combined mass of the iron-based soft magnetic powder, the condensed aluminum phosphate layer and the silicone resin layer, and the mass ratio of the condensed aluminum phosphate layer to the combined mass of the condensed aluminum phosphate layer and the silicone resin layer are substantially the same as the amounts of the iron-based soft magnetic powder, the condensed aluminum phosphate powder and the silicone resin used in the preparation of the iron-based soft magnetic powder for the powdered magnetic core, and can be controlled by adjusting the amounts of these raw materials.
[0083] <Powdered Magnetic Core>
[0084] The powder magnetic core can be obtained by filling a mold with the iron-based soft magnetic powder for the powder magnetic core of the present invention, pressing and molding the powder magnetic core into a desired shape, and then performing heat treatment.
[0085] The press molding method is not particularly limited, and a known molding method such as a room temperature molding method and a mold lubrication molding method can be used.
[0086] The molding pressure can be appropriately determined according to the application, but is preferably 10 t / cm2 from the viewpoint of obtaining a high density of the molded body. 2 More preferably 15t / cm 2 above.
[0087] During pressure molding, a lubricant can be applied to the mold wall or added to the powder as needed. By using a lubricant, the friction between the mold and the powder can be reduced during pressure molding, and the reduction in the density of the molded body can be suppressed. In addition, the friction when the mold is pulled out can be reduced, and the cracking of the molded body (compressed powder body) when taken out can be prevented. As a lubricant, metal soaps such as lithium stearate, zinc stearate, and calcium stearate, and waxes such as fatty acid amides are preferred.
[0088] Heat treatment after press forming can be performed at a temperature of 500° C. to 900° C. In order to release the strain caused by forming, heat treatment at 500° C. or higher, preferably 550° C. or higher, is required. On the other hand, if the temperature is 900° C. or lower, it is easy to avoid the situation where the microstructure is refined due to the γ phase transformation and the magnetic properties are deteriorated.
[0089] The temperature increase or decrease during the heat treatment may be set to a stage where a certain temperature is maintained.
[0090] The heat treatment may be performed in the air, in an inert atmosphere (eg, a nitrogen atmosphere), in a reducing atmosphere, or in a vacuum. It is considered that there is no problem in selecting any atmosphere.
[0091] The dew point of the atmosphere can be appropriately determined according to the application.
[0092] The temperature increase or decrease during the heat treatment may be set to a stage where a certain temperature is maintained.
[0093] Example
[0094] Next, the present invention will be described in more detail based on examples. The present invention is not limited to the examples.
[0095] The materials used in the examples are as follows.
[0096] Iron-based soft magnetic powder: apparent density is 3.0Mg / m 3, water atomized pure iron powder with an average particle size (D50) of 100μm.
[0097] Aluminum tripolyphosphate powder: K-FRESH #100P manufactured by TAYCA Co., Ltd. Powder with an average particle size of 5 μm.
[0098] Silicone resin 1: SR2400 manufactured by Dow Corning Toray
[0099] Silicone resin 2: KR-220LP manufactured by Shin-Etsu Chemical Co., Ltd.
[0100] Silicone resin 3: TREFIL R-910 manufactured by Dow Corning Toray
[0101] Aluminum phosphate (AlPO4): manufactured by Wako Pure Chemical Industries, Ltd., purity 97%
[0102] Evaluations of the Examples were as follows.
[0103] Density: Measure the size and weight of the test piece and calculate the density. 7.51Mg / m 3 The above are target values.
[0104] Resistivity: measured by a four-terminal method. Based on the study of Fujita et al. (Fujita Yuichiro, Saito Takashin: Electric Steel, 79 (2008) p. 109-117), the target value is 100 μm or more, which is sufficient to suppress eddy current loss.
[0105] Iron loss characteristics: The test piece was wound (100 turns for the primary winding and 20 turns for the secondary winding), and the hysteresis loss (1.0 T, 1 kHz, DC magnetization measuring instrument manufactured by Metron Technology Co., Ltd.) and iron loss (1.0 T, 1 kHz, high-frequency iron loss measuring instrument manufactured by Metron Technology Co., Ltd.) were measured. Eddy current loss was calculated from these measured values.
[0106] <Example 1>
[0107] The iron-based soft magnetic powder and aluminum tripolyphosphate powder were put into a high-speed mixer (LFS-GS-2J type, manufactured by EarthTechnica) in the amounts shown in Table 1. The atmosphere in the stirring tank was nitrogen, the heater temperature of the stirring tank was set to 190°C, and the stirring was performed for 20 minutes at a blade speed of 500 rpm. The highest temperature reached during stirring was 168°C. Thereafter, the powder was cooled to 60°C in the stirring tank, and the powder having the aluminum tripolyphosphate layer was discharged from the stirring tank. By SEM observation, the aluminum tripolyphosphate layer formed a continuous film on the surface of the particles in the iron-based soft magnetic powder. The highest temperature reached is the highest temperature among the temperatures shown by the thermocouple in the stirring tank.
[0108] In Example 1, a silicone resin was used as the silicone resin 1.
[0109] The silicone resin was dissolved in toluene to prepare a resin dilution solution (solid content concentration of the silicone resin: 2.0% by mass). The iron-based soft magnetic powder having an aluminum tripolyphosphate layer was immersed in the resin dilution solution in an amount as described in Table 1, and after gently stirring, the organic solvent was dried and then heat-treated at 200° C. for 120 minutes in the atmosphere to form a silicone resin layer.
[0110] The obtained powder having a silicone resin layer was filled into a mold coated with a lubricant and molded at a molding pressure of 15 t / cm 2 The molded body was molded into a ring shape with an outer diameter of 38 mm, an inner diameter of 25 mm, and a height of 6 mm. The obtained molded body was heat treated in nitrogen at 600° C. for 45 minutes to obtain a test piece.
[0111] The density, resistivity, and magnetic properties of the obtained test pieces were evaluated.
[0112]
[0113] According to Table 1, No. 2 to 6 and 9 to 13, which have both an aluminum tripolyphosphate layer and a silicone resin layer, have high density and achieve the target resistivity. Comparing No. 1 and N. 7, which have the same total amount of the aluminum tripolyphosphate layer and the silicone resin layer but only have one layer, with No. 2 to 6, it can be seen that No. 2 to 6 has a significantly high resistivity. Similarly, comparing No. 8 and No. 14 with No. 9 to 13, it can be seen that No. 9 to 13 has a significantly high resistivity. No. 2 to 6 and No. 9 to 13 show low iron loss, but this is because the effect of suppressing eddy current loss is high.
[0114] <Example 2>
[0115] In Example 2, a powder (No. 15) having a phosphate-based coating and a silicone resin layer was prepared for comparison. Silicone resin 1 was used as the silicone resin.
[0116] 1 kg of iron-based soft magnetic powder was put into a high-speed mixer (manufactured by EarthTechnica, high-speed mixer model LFS-GS-2J). The atmosphere in the stirring tank was nitrogen. 12 g of aluminum phosphate aqueous solution (solid content concentration of aluminum phosphate: 10% by mass) was sprayed from the top of the stirring tank using nitrogen at a liquid delivery rate of 2 g / min for 6 minutes.
[0117] After spraying, the temperature in the stirring tank was heated to 120° C. and stirred in a nitrogen atmosphere for 10 minutes to evaporate water. Thereafter, the powder was cooled to 60° C. in the stirring tank, and the powder having the aluminum phosphate chemical coating was discharged out of the stirring tank.
[0118] The obtained powder having a chemical conversion film of aluminum phosphate was subjected to the same process as in Example 1, using a resin dilution solution in an amount of 0.08 mass % of the silicone resin layer in the powder after the silicone resin layer was formed, thereby forming a silicone resin layer.
[0119] The obtained powder having a silicone resin layer was formed into a molded body in the same manner as in Example 1, and subjected to heat treatment to obtain a test piece.
[0120] For comparison, a powder (No. 16) was prepared in which a silicone resin layer was formed on a powder obtained by mixing an iron-based soft magnetic powder and an aluminum tripolyphosphate powder without heating.
[0121] The powder obtained by mixing the iron-based soft magnetic powder and the aluminum tripolyphosphate powder without heating was observed by SEM, and the granular aluminum tripolyphosphate was attached to the iron-based soft magnetic powder. The mixed powder was subjected to the same method as in Example 1 using the resin dilution solution of the silicone resin 1 to form a silicone resin layer.
[0122] The obtained powder having a silicone resin layer was formed into a molded body in the same manner as in Example 1, and subjected to heat treatment to obtain a test piece.
[0123] The amounts of the iron-based soft magnetic powder, aluminum tripolyphosphate powder, and silicone resin 1 in No. 16 are the same as those in No. 4 of Example 1.
[0124] The density, resistivity, and magnetic properties of these test pieces and the test piece No. 4 of Example 1 were evaluated. The results are shown in Table 2.
[0125] Table 2
[0126]
[0127] According to Table 2, the iron loss of No. 4 is lower than that of No. 15, and it can be seen that the main reason is the improvement of hysteresis loss. As a reason, it is estimated that in No. 15, aluminum phosphate aqueous solution is used, and oxidation of iron powder occurs during the chemical treatment, which increases hysteresis loss. In contrast, in No. 4, the dry method is used, so oxidation is suppressed.
[0128] The resistivity of No. 16 did not reach the target value. The iron loss of No. 4 was lower than that of No. 16, and it was found that the main reason was the high eddy current loss suppression effect.
[0129] <Example 3>
[0130] In Example 3, the method for forming the silicone resin layer in No. 4 of Example 1 was changed to a dry method for evaluation.
[0131] As the silicone resin, silicone resin 2 was used in No. 17, and silicone resin 3 was used in No. 18.
[0132] An iron-based soft magnetic powder having an aluminum tripolyphosphate layer is prepared in the same manner as No. 4 in Example 1, and the powder and silicone resin are put into a high-speed blender (manufactured by EarthTechnica, high-speed blender model LFS-GS-2J) in the amounts shown in Table 3. The blade speed is 1000 rpm. The stirring is terminated when the temperature in the stirring tank reaches 50°C, and the powder having the silicone resin layer is discharged out of the stirring tank.
[0133] The powder having the obtained silicone resin layer was formed into a molded body in the same manner as in Example 1, and subjected to heat treatment to obtain a test piece.
[0134] The density, resistivity, and magnetic properties of the obtained test pieces were evaluated.
[0135] Table 3
[0136]
[0137] No. 17 and 18, in which the method for forming the silicone resin layer was changed to a dry method, showed a density and resistivity equivalent to those of No. 4 formed by a wet method, and exhibited low iron loss.
[0138] Industrial Applicability
[0139] The powder magnetic core using the iron-based soft magnetic powder for a powder magnetic core of the present invention has a high density, and therefore can improve the magnetic flux density, and is expected to have a high motor torque. In addition, the iron loss is also low, and therefore the usefulness is high.
Claims
1. An iron-based soft magnetic powder for a powder magnetic core, wherein the surface of particles in the iron-based soft magnetic powder has a condensed aluminum phosphate layer, and the surface of the condensed aluminum phosphate layer has a silicone resin layer, The condensed aluminum phosphate layer is a continuous film. The total mass of the condensed aluminum phosphate layer and the silicone resin layer is 0.10% to 0.60% by mass in the total mass of the iron-based soft magnetic powder, the condensed aluminum phosphate layer and the silicone resin layer (100% by mass). The mass ratio of the condensed aluminum phosphate layer to the total mass of the condensed aluminum phosphate layer and the silicone resin layer is 0.2 to 0.
9.
2. A powder magnetic core, which is obtained by pressing and molding the iron-based soft magnetic powder for the powder magnetic core according to claim 1 and subjecting it to heat treatment.
3. A method for producing an iron-based soft magnetic powder for a powder magnetic core, wherein the particles in the iron-based soft magnetic powder have a condensed aluminum phosphate layer on their surfaces and a silicone resin layer on the surface of the condensed aluminum phosphate layer. The method comprises the following steps: heating and mixing an iron-based soft magnetic powder and a condensed aluminum phosphate powder to obtain an iron-based soft magnetic powder having a condensed aluminum phosphate layer on the surface, and then attaching an organic silicone resin to the surface of the condensed aluminum phosphate layer to form an organic silicone resin layer. In the total mass of the iron-based soft magnetic powder, the condensed aluminum phosphate powder and the silicone resin (100 mass%), the total mass of the condensed aluminum phosphate powder and the silicone resin is 0.10 mass% to 0.60 mass%, The mass ratio of the condensed aluminum phosphate powder to the total mass of the condensed aluminum phosphate powder and the silicone resin is 0.2 to 0.
9.
4. The method for producing an iron-based soft magnetic powder for a powder magnetic core according to claim 3, wherein: The maximum temperature reached during heating and mixing is 100°C to 200°C.
5. The method for producing an iron-based soft magnetic powder for a powder magnetic core according to claim 3 or 4, wherein: A solution in which a silicone resin is dissolved in an organic solvent and the iron-based soft magnetic powder having a condensed aluminum phosphate layer are kneaded and then dried to allow the silicone resin to adhere to the surface of the condensed aluminum phosphate layer.
6. The method for producing an iron-based soft magnetic powder for a powder magnetic core according to claim 3 or 4, wherein: The solid silicone resin is mixed with the iron-based soft magnetic powder having the condensed aluminum phosphate layer, so that the silicone resin is attached to the surface of the condensed aluminum phosphate layer.
7. A method for manufacturing a powdered magnetic core, comprising the following steps: filling a mold with the iron-based soft magnetic powder for a powdered magnetic core according to claim 1 or the iron-based soft magnetic powder for a powdered magnetic core obtained by the method for manufacturing the iron-based soft magnetic powder for a powdered magnetic core according to any one of claims 3 to 6, and performing heat treatment at a temperature of 500°C to 900°C after pressure molding.
